2019
DOI: 10.5194/acp-19-6637-2019
|View full text |Cite
|
Sign up to set email alerts
|

Personal exposure to PM<sub>2.5</sub> emitted from typical anthropogenic sources in southern West Africa: chemical characteristics and associated health risks

Abstract: Abstract. Urbanization is an issue that is strongly emerging in southern West Africa (sWA). There is a lack of full understanding on chemical compositions and personal exposure levels to fine particulate matter (hereafter defined as PE PM2.5) and its health risks related to various anthropogenic sources in this region. In this study, PE PM2.5 was studied in dry (January) and wet (July) seasons of 2016 for the first time to characterize the contributions of a domestic fire site (DF) to the exposure of women and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 91 publications
2
23
1
Order By: Relevance
“…where [X] atm and [Al] atm are the concentrations of the chemical element X and Al in the atmosphere, respectively, and [X] soil and [Al] soil are the typical concentrations of the element X and Al in the earth's crust, respectively. Al is frequently used as a reference element, assuming that its anthropogenic sources in the atmosphere are negligible (Gao et al, 2002;Cao et al, 2005;Xu et al, 2012). In all sampling sites, EF values typically lower than 5 are obtained for several trace elements (Be, Sc, Ti, V, Fe, Ga, Sr, Nb, Rh, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ta, Th, and U).…”
Section: Trace Element Concentrationsmentioning
confidence: 99%
“…where [X] atm and [Al] atm are the concentrations of the chemical element X and Al in the atmosphere, respectively, and [X] soil and [Al] soil are the typical concentrations of the element X and Al in the earth's crust, respectively. Al is frequently used as a reference element, assuming that its anthropogenic sources in the atmosphere are negligible (Gao et al, 2002;Cao et al, 2005;Xu et al, 2012). In all sampling sites, EF values typically lower than 5 are obtained for several trace elements (Be, Sc, Ti, V, Fe, Ga, Sr, Nb, Rh, Ba, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Ta, Th, and U).…”
Section: Trace Element Concentrationsmentioning
confidence: 99%
“…Here, time activity is modelled based on available data for the region based on questionnaires. Modelling mobility patterns using smartphones with built-in GPS is an emerging trend in personal exposure assessment (Yu et al, 2019). Combining GPS-derived data on the trajectories of large number of individuals with information from questionnaires on the locations and activities of the population could help overcome a large part of the uncertainties relating to the time activity module developed in this study.…”
Section: Modelling the Activity Sequencesmentioning
confidence: 99%
“…Fan et al [ 77 ] performed personal sampling on 46 volunteers living in Hong Kong and detected a contribution of 46.8 ± 13.4% of carcinogenic PAHs in the total 16 PAHs. Xu et al [ 78 ] conducted personal sampling on subjects who were directly impacted by anthropogenic sources in an urbanizing region in southwest Africa and found that women’s (exposed to the emission of domestic cooking and heating, 77.4 ng/m 3 ) exposure concentration to 19 PAHs was 1.6 and 2.1 times that of students (exposed to waste burning discharge, 49.9 ng/m 3 ) and drivers (exposed to vehicle emission, 37.0 ng/m 3 ), respectively. Wei et al [ 79 ] measured the 24-h PAH exposure level on security guards, which was mainly generated from vehicular emission, and found it was related to increasing oxidative burdens.…”
Section: Evaluation Methodsmentioning
confidence: 99%
“…After loading, PAHs are extracted from the collection materials and analyzed by techniques such as high-performance liquid chromatography and gas chromatography-mass spectrometry. Filter-based sampling can generate a comprehensive pollution profile with the characterization and specified quantification of individual and total PAHs, with multi-particulate sizes and particulate and gaseous phase distributions, as well as the simultaneous PM concentration and other PM-containing constituents if available [ 72 , 73 , 78 , 81 ]. Nevertheless, active samplers can burden users with pump noise and equipment weight.…”
Section: Evaluation Methodsmentioning
confidence: 99%
See 1 more Smart Citation